The Phenomenon of Metafiction in China: Theoretical and Historical Aspects - Лю Мяовэнь (Philology & Human, 2020)
The article deals with a phenomenon called metafiction. This phenomenon, thoroughly studied by Western European and American philologists, is now considered basing on Chinese literature – from the first publications in the late 1980s to modern monographs; the paper gives a brief introduction into scientific articles and monographs of Chinese and Russian scholars who played a key role in the study of metafiction. The author of the article identifies its main features and summarizes the existing concepts of Chinese literary scholars. Particular attention is paid to the «Chinese characteristics» of metafiction. The author distinguishes the differences between the concepts of «metafiction» and «metafictional»: while the former is primarily associated with modern Chinese literature, the latter is used more widely and is even applied to ancient Chinese novels. The article also shows the evolution of the attitude of Chinese literary scholars towards metafiction: from agreement with Western scholars to the emergence of dialogue with them. To sum up, the author of the article describes unresolved problems of this phenomenon and prospects for the study of it in detail.